Texture Dirac Mass Matrices and Lepton Asymmetry in the Minimal Seesaw Model with Tri-Bimaximal Mixing: Agus Purwanto, Bintoro Anang Subagyo, Erika Rani - Agus Purwanto, Agus Purwanto; Bintoro Anang Subagyo, Bintoro Anang Subagyo; Erika Rani, Erika Rani (Jurnal Fisika dan Aplikasinya, 2025)
We examined the minimal seesaw mechanism of 3 × 2 Dirac matrix by starting our analysis with the masses of light neutrinos with tri/bi-maximal mixing in the basis where the charged-lepton Yukawa matrix and heavy Majorana neutrino mass matrix are diagonal. We found all possible Dirac mass textures which contain one zero entry or two in the matrix.